Enhancing Junior High School Students' Learning Outcomes through a Differentiated PjBL-Based Interactive E-Module with Flipped Classroom Approach - Fitriani R, Rosa; Mursid, R.; Tanjung, Samsidar (IJOEM Indonesian Journal of E-learning and Multimedia, 2025)
Background: The integration of technology into education, especially in language learning, plays a vital role in improving student engagement and understanding. Procedure texts, a common genre in English classes, often pose comprehension challenges when taught using traditional methods.Aims: This study aims to develop and evaluate an interactive e-module based on the Project-Based Learning (PjBL) model and the flipped classroom approach to enhance students’ cognitive abilities and engagement in learning procedure texts.Methods: The e-module was developed using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). Data collection involved pre- and post-tests, expert validations, and surveys administered to both students and teachers. Effectiveness was measured using statistical analyses, including t-tests and N-Gain calculations.Results: Findings revealed a significant improvement in students’ performance, with the experimental group’s mean score increasing from 14.50 (pre-test) to 20.93 (post-test) and an N-Gain score of 0.66, indicating a high level of learning effectiveness. Expert validation and user feedback confirmed the e-module’s practicality, interactivity, and educational value.Conclusion: The developed e-module effectively enhanced students' understanding of procedure texts, demonstrating the benefits of combining digital tools with active learning models like PjBL and the flipped classroom. This research contributes to the advancement of interactive learning media in language education.